2014
DOI: 10.1177/0308575914543235
|View full text |Cite
|
Sign up to set email alerts
|

Attachment representations in late-adopted children: the use of narrative in the assessment of disorganisation, mentalising and coherence of mind

Abstract: Late-adopted children have often suffered a wide range of deprivations in their pre-adoption lives. These early adverse experiences can have a negative effect on children’s attachment representations even after they have been adopted. This study assesses the attachment representations of 61 late-adopted children over the first year of placement, exploring the risk and protective factors of age at placement, length of adoption and gender. The attachment representations were captured using the Manchester Complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…However, several European studies have emerged in recent years covering a wide range of adoption related matters, though much of this literature pays limited attention to education as a primary focus, instead concentrating on psycho-social development (e.g. Molina et al, 2015;Pace et al, 2014;Soares et al, 2017), policy implications (e.g. Rees and Selwyn, 2009), or solely sampling children placed through Inter-Country Adoption (ICA; e.g.van der Voort et al, 2014;Beckett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, several European studies have emerged in recent years covering a wide range of adoption related matters, though much of this literature pays limited attention to education as a primary focus, instead concentrating on psycho-social development (e.g. Molina et al, 2015;Pace et al, 2014;Soares et al, 2017), policy implications (e.g. Rees and Selwyn, 2009), or solely sampling children placed through Inter-Country Adoption (ICA; e.g.van der Voort et al, 2014;Beckett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the children raised in institutions suffer from a severe socioemotional deprivation and do not form attachments towards their institutional caregivers (Smyke et al 2002;Zeanah et al 2005). Adopted children have been described as showing reactive attachment disorders and indiscriminate friendly behavior (Zeanah 2000;Zeanah et al 2004): adverse preadoption rearing settings can, therefore, lead to insecure or disorganized attachment representations (Chisholm et al 1995;Hodges et al 2011;Pace et al 2014;Pace et al 2015a;Palacios et al 2005;van IJzendoorn and Juffer 2006;Vorria et al 2003), which, in turn, can result in adverse developmental outcomes (Juffer and van IJzendoorn 2005;Van den Dries et al 2009;van IJzendoorn et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Globally adoption research, on the one hand, has pointed out that late-adopted children are at high risk for elevated rates of socio-emotional and behavioural difficulties, including insecure/disorganized attachment patterns and internalizing and externalizing behaviour problems; on the other hand, high resilience, capacity of recovery from early deprivation, ability to build positive representations of new caregivers, and earned attachment security emerged in adopted children and their adoptive families (Barone & Lionetti, 2012;Bimmel, Juffer, van IJzendoorn, & Bakermans-Kranenburg, 2003;Pace & Zavattini, 2011;Pace, Cavanna, Velotti, & Zavattini, 2014;. Recent longitudinal attachmentbased studies on adoption and maternal sensitivity showed that more sensitive parenting -in infancy middle childhood, and/or adolescence-predicted continuity of secure attachment of adopted children from infancy to adolescence, less inhibited and delinquent behaviours in adolescence and secure attachment representations in young adulthood (Beijersbergen, Juffer, Bakermans-Kranenburg, & van IJzendoorn, 2012;Pace, Di Folco, Guerriero, Santona, & Terrone, 2015a;Schoenmaker et al, 2015a; IJzendoorn, 2013;van der Voort et al, 2014).…”
Section: Introductionmentioning
confidence: 99%